2017
DOI: 10.5812/aapm.14426
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Doses of Intrathecal Hyperbaric Bupivacaine Plus Sufentanil in Spinal Anesthesia for Cesarean Sections

Abstract: BackgroundDecreasing side effects and improving the quality of block in caesarean sections by appropriate dosage of local anesthetics and adjuvants could play an important role in the safe management of cesarean section. The present study aimed at comparing the effects of 3 different doses of intrathecal hyperbaric bupivacaine injected with a fixed dose of sufentanil in cesarean sections.MethodsIn a double- blind randomized clinical trial, 105 candidates of elective cesarean section were randomly assigned into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…It is worthy of note that the frequency of maternal nausea and vomiting was low. Similar rates were reported in studies where low doses of LA were used [14,28]. Therefore, the results of our study do not support the notion that adjusting conventional doses of bupivacaine to patient's height will prevent nausea and vomiting.…”
Section: Discussioncontrasting
confidence: 53%
“…It is worthy of note that the frequency of maternal nausea and vomiting was low. Similar rates were reported in studies where low doses of LA were used [14,28]. Therefore, the results of our study do not support the notion that adjusting conventional doses of bupivacaine to patient's height will prevent nausea and vomiting.…”
Section: Discussioncontrasting
confidence: 53%
“…This was likely because these patients received a higher dose of phenylephrine. Alimian et al [24] , reported that mean preoperative MAP was comparable in three groups (8mg, 9mg, 10mg). The trend of MAP was comparable in the 3 groups even after anesthetic dose (P>0.05).…”
Section: Mean Arterial Pressurementioning
confidence: 96%
“…(Table 4) Other comparative studies also had no significant difference in the demographic variables among the groups. [21][22][23][24][25][26][27] Cenkowski et al [22] , reported that the average age in the conventional dose group was 31±3 versus 32 ± 6 years in the low dose group, Venkata et al [25] , study group had comparable mean age of the patients (24±2.1 vs 23±1.5); comparable weight (68±5.0 vs 64±4.84); comparable height (156±6.5 vs 158±9.0); and comparable ASA status (I/II vs I/II) (P>0.05), Mebazaa et al [20] as compared to conventional dose group (Group A), low-dose Group (Group B) had similar age (33 ± 6 vs 32 ± 5); similar weight (78 ± 10 vs 77 ± 9); similar height (…”
Section: Demographic Datamentioning
confidence: 99%
“…Administration of an appropriate dose hyperbaric bupivacaine can minimize potential side effects while improving block quality ( 18 ). However, the optimal intrathecal dose of hyperbaric bupivacaine for SPA is still being debated.…”
Section: Introductionmentioning
confidence: 99%